Peningkatan Hasil Belajar Peserta Didik Kelas III C Melalui Model PBL Menggunakan Media Audiovisual - Reza Tegar Rizqiana; Widya Kusumaningsih; Nur Riskiyati (STKIP Andi Matappa Pangkep, 2024)
Action research was conducted to improve the learning outcomes of grade III C students in thematic learning at SDN Karanganyar Gunung 02. Problem Based Learning (PBL) using audiovisual media was chosen as the instructional model. The research was carried out over two cycles, starting with a pre-cycle phase. Each cycle involved revisions to the lesson plans (RPP) and media used. The results showed that implementing the Problem Based Learning model with audiovisual media significantly enhanced students' learning outcomes. In the pre-cycle phase, the average score of students was 60 with a percentage of 21.4%. By Cycle I, the average score increased to 75.5 with a percentage of 75%. In Cycle II, the average score further improved to 88.5 with a percentage of 92.8%. In conclusion, Problem Based Learning using audiovisual media proves to be effective in enhancing students' learning outcomes in thematic subjects.